2021
DOI: 10.1093/molbev/msab304
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Neanderthal Adaptively Introgressed Genetic Variants That Modulate Reporter Gene Expression in Human Immune Cells

Abstract: Summary Paragraph While some variation introgressed from Neanderthals has undergone selective sweeps, little is known about its functional significance. We used a Massively Parallel Reporter Assay (MPRA) to assay 5,353 high-frequency introgressed variants for their ability to modulate the gene expression within 170bp of endogenous sequence. We identified 2,548 variants in active putative cis-regulatory elements (CREs) and 292 expression-modulating variants (emVars). These emVars are predicted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…These include prediction models to impute unobserved differences in gene expression and 3D genome organization (43, 44); CRISPR-Cas9 editing of archaic alleles into human-derived stem cells (45, 46); and massively parallel reporter assays (MPRAs) to identify causal variants with cis-regulatory impacts on transcription (4749). In particular, MPRAs have been applied to study modernspecific and adaptively introgressed variants (5053). Most of these studies focused on transcriptional regulation even though post-transcriptional processes, such as RNA splicing regulation, are also important to human phenotypes and disease (5457).…”
Section: Introductionmentioning
confidence: 99%
“…These include prediction models to impute unobserved differences in gene expression and 3D genome organization (43, 44); CRISPR-Cas9 editing of archaic alleles into human-derived stem cells (45, 46); and massively parallel reporter assays (MPRAs) to identify causal variants with cis-regulatory impacts on transcription (4749). In particular, MPRAs have been applied to study modernspecific and adaptively introgressed variants (5053). Most of these studies focused on transcriptional regulation even though post-transcriptional processes, such as RNA splicing regulation, are also important to human phenotypes and disease (5457).…”
Section: Introductionmentioning
confidence: 99%
“…Although we are able to detect tissue- and allele-specific effects, there are still limitations in WhAMPRA’s in vivo technology. In contrast to the hundreds of enhancers we profile, current cell culture reporter assays can provide quantitative, cell line-specific information across thousands of enhancers 17,27,53 . Efficient transduction of tissue is likely the current limitation in the technology.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to effectively deliver plasmid libraries of hundreds-to-thousands of candidate enhancers to cultured cells has allowed for detailed, quantitative descriptions of how subtle differences in genome sequence relate to differences in cell type-specific gene regulation. Studies have used reporter assay techniques to measure the effects of single nucleotide polymorphisms (SNPs) identified from expression quantitative trait loci studies (eQTLs) 19,20 , SNPs from genome-wide association studies (GWAS) [24][25][26] , and human lineage-specific mutations 27,28 . High-throughput reporter assays have also been adapted to study gene regulation in cultured neurons 18,29 .…”
Section: Main Textmentioning
confidence: 99%
“…Second, the eQTLGen trans-eQTL screen includes a link between two aSNPs in the STAT2 region and IFI16, a predicted target of STAT2 , adding an empirical example that is consistent with the TF target gene prediction for this TF. Third, a recent study that experimentally tested aSNPs for their regulatory potential to modulate gene expression identified aSNPs with such a potential and using CRISPR technologies demonstrated that three of the detected variants modified the expression of STAT2 in an immune cell line (Table S12, (Jagoda et al, 2021)).…”
Section: Discussionmentioning
confidence: 99%